THE ROLE OF ENABLER FACTORS ON SUCCESS OF KNOWLEDGE MANAGEMENT IN STATE CORPORATIONS: A CASE OF KENYA WILDLIFE SERVICES - Cherutich, Christine Jeptoo; Nyiro, Dr. Charles (Human Resource and Leadership Journal, 2019)
Purpose: The objectives of the study which were to determine the effects of leadership, technology, culture, people and knowledge management success as enabler factors in ensuring success of knowledge management in Kenya Wildlife Service. The research also draws on existing studies, frameworks and models that have already identified the factors that potentially affect the success of KM. Meeting the challenges of sustainable development in the 21st century necessitates utilization of vital disciplines like KM in the management of state corporations. The use of KM for sustainable development has shown that effectiveness depends on strategic planning and use of tested models. Methodology: A review of the literature shows that most models point to enablers that are necessary. Questionnaires were administered through both e- mails and hand delivery. Secondary data was obtained from both published and unpublished records. Questionnaires were tested for both reliability and validity. Qualitative and quantitative techniques were used to analyze data with the assistance of SPSS software program version 21. Results: A good response rate of 94% was realized. It was established that most of the enabler's factors indicators have positive impact on success of knowledge management. The study further adopted a regression analysis to determine the relationship between the variables at 5% confidence level of significance. The study findings showed that the four variables had a significant influence on performance of the firm. Contribution to policy and practice: The study recommended that a similar research should be conducted in a different fields. The findings showed that 74.7 % of the knowledge management success is explained by the four variables that are leadership, culture, technology and people and the remaining 25.3 % can be accounted by the standard error.